Effect of Activated Charcoal on Bovine Enamel Shade/ Karen Joy A. Donila and Kathleen Marie A. Ferrer. - Donila, Karen Joy A.; Ferrer, Kathleene Marie A.; Rebueno Santos, Jessica (2023)
INTRODUCTION: People try to improve their smile by having whiter teeth. While
there is an obvious demand for teeth whitening products and services, not
everyone can afford them. As a result, people may resort to Do it Yourself versions
of these practices because they are cheaper alternatives to teeth whitening. The
one gaining internet popularity is whitening teeth using activated charcoal.
METHODS: A completely randomized study was done. Forty-five bovine teeth
specimens were allocated into: water group, Colgate® Optic White group, and
activated charcoal group. The specimens were subjected to 14 days of tooth
brushing. Digital photography was done using a DSLR camera during baseline,
day 7, and day 14. L*a*b color parameters were read using Adobe Photoshop CS6.
The Delta E values computed were compared using paired samples t-tests and
Levene’s test for the homogeneity of variances.
RESULTS: The average Delta E values computed for activated charcoal (ΔE=7),
Colgate® Optic White (ΔE=5), water (ΔE=6), imply that the shade change is
perceptible to the human eye at a glance. L*a*b results reveal that the direction of
shade change is leaning towards whitening for the activated charcoal group.
However, p values for activated charcoal (p-value= 0.060), Colgate® Optic White
(p-value= 0.751), and water (p-value= 0.256) did not produce statistically xiii
significant changes in the shade of bovine teeth. Among the three, activated
charcoal is the most significant as it has the lowest p-value.
CONCLUSION: While a clinically perceived shade change was observed, there is
lack of statistical evidence to conclude that activated charcoal can produce
significant shade changes in the enamel of the bovine teeth samples.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Charcoal -- Dental care .; Bovine teeth